2019
DOI: 10.1186/s12882-019-1669-3
|View full text |Cite
|
Sign up to set email alerts
|

Removal of large middle molecules via haemodialysis with medium cut-off membranes at lower blood flow rates: an observational prospective study

Abstract: Background: Online haemodiafiltration (OL-HDF) may improve middle molecular clearance in contrast to conventional haemodialysis (HD). However, OL-HDF requires higher convective flows and cannot sufficiently remove large middle molecules. This study evaluated the efficacy of a medium cutoff (MCO) dialyser in removing large middle molecular uraemic toxins and compared it with that of conventional high-flux (HF) dialysers in HD and predilution OL-HDF. Methods: Six clinically stable HD patients without residual re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 36 publications
6
32
0
Order By: Relevance
“…These findings have been replicated in a small (N = 6) study from South Korea demonstrating greater albumin losses with an MCO membrane (Theranova 400; median 3.16 g per session) than with a high flux membrane (Rexeed™-21A; Asahi Kasei Medical Co., Ltd., Tokyo, Japan; median 0.06 g per session). 61 The loss of albumin with MCO dialyzers does not appear to be impacted by increasing the membrane surface from 1.7 m 2 (Theranova 400) to 2.0 m 2 (Theranova 500 TM ; Baxter Healthcare Corporation, Deerfield, IL, USA). 62 In summary, the median albumin loss per HD session with MCO dialyzers appears to be approximately 3 g, with some variability across individuals.…”
Section: Impact Of Different Dialyzers On Albumin Levelsmentioning
confidence: 93%
“…These findings have been replicated in a small (N = 6) study from South Korea demonstrating greater albumin losses with an MCO membrane (Theranova 400; median 3.16 g per session) than with a high flux membrane (Rexeed™-21A; Asahi Kasei Medical Co., Ltd., Tokyo, Japan; median 0.06 g per session). 61 The loss of albumin with MCO dialyzers does not appear to be impacted by increasing the membrane surface from 1.7 m 2 (Theranova 400) to 2.0 m 2 (Theranova 500 TM ; Baxter Healthcare Corporation, Deerfield, IL, USA). 62 In summary, the median albumin loss per HD session with MCO dialyzers appears to be approximately 3 g, with some variability across individuals.…”
Section: Impact Of Different Dialyzers On Albumin Levelsmentioning
confidence: 93%
“…MCO is a novel type membrane for HD. In a study performed by Kim et al, it was showed that HD with MCO membranes achieved signi cantly greater reduction ratio of large middle molecules (including cytokines such as IL-1 and IL-6), than HD with conventional membranes and online-hemodio ltration [19].…”
Section: Discussionmentioning
confidence: 99%
“…Three type of hemodialysis membranes are described: low ux (LF), high ux (HF) and medium cut-off (MCO) [18]. MCO membranes may make greater clearances and intradialytic reduction ratios for large-middle molecules (including cytokines) than LF and HF membranes [19].…”
Section: Introductionmentioning
confidence: 99%
“…No significant differences in the RRs of small and middle molecules, and the global removal scores were observed between MCO and HDF dialyzers. MCO dialyzer membranes even may allow the removal of larger uraemic toxins not previously targeted by current maintenance HD techniques [26,27]. The MCO dialyzer membranes offer effective retention of bacterial products from conventional dialysis fluid without requiring an ultrapure water supply or other HDF infrastructure [28].…”
Section: Expanded Haemodialysis (Hdx): An Emerging Alternative To Higmentioning
confidence: 99%